PERAN CERITA ANAK UNTUK MENGURANGI PENGGUNAAN TELEPON GENGGAM DI YAYASAN RUHAMA GUNUNG SINDUR - Rerin Maulinda; Melda Widayanti Okta; Melisa Dwi Utami (Jurnal Kabar Masyarakat, 2023)
Fairy tales are one of the fun learning approaches for children. Through fairy tales with stories that are interesting to children, it can make it easier for children to absorb information. The benefits of writing the first fairy tale to be able to invite to work on new vocabulary for children. The purpose of this study is to help the children of Ruhama Foundation Hidayatullah Islamic Boarding School to learn moral values through stories with storytelling activities. The method used in this study is qualitative descriptive method. Qualitative descriptive method is a method to find knowledge or theory of research at a certain time. The results of research that have been conducted by researchers on improving the character, creativity and morals of children through the role of children's stories to reduce the use of mobile phones, after carrying out research and observations researchers can draw a conclusion, that character, creativity, and morals in children are one of the most important things to form a good personality. If a child can be educated about creativity, character and morals that are sufficient both from teachers and parents in every development this will have an impact on the child and can affect every attitude and nature in his growth towards adulthood, the growth and development mechanism of children who get a good education will be formed along with the habits they see. This will form a belief in what the child will believe someday.